Fourteen new species of demosponges (Porifera) from three coastal fjords in southern British Columbia, Canada - Ott, B.; Mcdaniel, N.; Humphrey, E. (Zootaxa, 2024)
Collections of encrusting sponges from the shallow subtidal zone of three southern fjords in British Columbia, Canada, and adjacent waters provided the material for the description of 14 new species. Species represent 5 orders, 8 families and 11 genera providing a cross section of British Columbia shallow water fjord Demospongiae. New species include Eurypon reiswigi n. sp., E. scruposus n. sp., E. microtuberculatum n. sp., Hymeraphia pacifica n. sp., Hamigera bakusi n. sp., Hymedesmia (Hymedesmia) anvilensis n. sp., Hymetrochota austini n. sp., Discorhabdella atypica n. sp., Antho (Acarnia) flavoaurantiaca n. sp., Clathria (Microciona) aquaradiata n. sp., Hymeniacidon globularis n. sp., Oceanapia polytuba n. sp., O. flava n. sp., and Spongionella tenuis n. sp. Species range from uncommon to common both within and outside fjord environments. Range extensions of genera include: Eurypon, Northeast Pacific range extension from Mexico to BC; Hymeraphia, range extension to the Northeast Pacific, Hamigera, range extension to the Northeast Pacific, Hymetrochota, range extension to the Northeast Pacific and depth extension to shallow water, and Oceanapia, Northeast Pacific range extension from the Gulf of California to central BC.